2020
DOI: 10.1097/won.0000000000000691
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Acquired Pressure Injury Development Among Surgical Critical Care Patients Admitted With Community-Acquired Pressure Injury

Abstract: PURPOSE: Community-acquired pressure injuries (CAPIs) are present among approximately 3% to 8% of patients admitted to acute care hospitals. In the critical care population, little is known about hospital-acquired pressure injury (HAPI) development among patients with CAPIs because most studies exclude patients with CAPIs. The purpose of our study was to determine the incidence of HAPI development and the associated risk factors among surgical critical care patients with CAPIs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
5
1
1
Order By: Relevance
“…Of note, these common risk factors have been examined in the literature with varying results. 3,5,10 Surprisingly, some common factors discussed in the literature were found less frequently among our study participants, such as diabetes and having a ventricular assist device in place. 15,30 Qualitative results.…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…Of note, these common risk factors have been examined in the literature with varying results. 3,5,10 Surprisingly, some common factors discussed in the literature were found less frequently among our study participants, such as diabetes and having a ventricular assist device in place. 15,30 Qualitative results.…”
Section: Resultscontrasting
confidence: 55%
“…2 In a study by Alderden and colleagues that included 4,934 critical care patients who presented to the hospital with no preexisting PIs, 7% (n = 352) developed a HAPI; additionally, 50% of the stage 1 HAPIs worsened into more severe stages, although the study does not indicate the stages reached. 3 Patients who have undergone vascular surgery are at an elevated risk for developing PIs. A recent scop-ing review found that the incidence of PIs in these patients ranged from 17.2% to 45%, and varied according to procedure.…”
Section: Evaluating the Eff Ectiveness Of An Alternating Pressure Ove...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sağlık bakım sistemleri içerisinde kalite göstergelerinden biri olarak ele alınan ve hastanın gereksiz yere acı, ağrı çekmesine yol açan basınç yaralanmaları (BY) [1][2][3][4] , çoğunlukla "kemik çıkıntısı üzerinde, tıbbi ya da diğer bir cihazla ilgili ciltte ve/veya altta yatan yumuşak dokunun lokalize hasarı" olarak tanımlanmaktadır [4][5][6] . BY, sağlık bakım maliyetlerini, mortaliteyi, morbiditeyi ve hastanede kalış süresini arttırmakta, aynı zamanda hastanın ve ailenin yaşam kalitesini olumsuz yönde etkilemektedir.…”
Section: Introductionunclassified
“…Two of those-hemoglobin and serum albumin-are further evidence for the role of altered perfusion in HAPrI etiology. 1,22,34,35 Low levels of hemoglobin 36 and serum albumin 37,38 are previously identified HAPrI risk factors thought to affect tissue perfusion and therefore HAPrI risk through oxygen-carrying capacity (hemoglobin) and colloid osmotic pressure (serum albumin). 21 Furthermore, hemoglobin may be considered a modifiable factor, given that low levels can be corrected with blood transfusion; future research is needed to evaluate the effects of so-called permissive anemia 39 and blood transfusion on risk for HAPrI formation.…”
Section: Discussionmentioning
confidence: 99%